Programmed Cell Deaths and Potential Crosstalk With Blood–Brain Barrier Dysfunction After Hemorrhagic Stroke - Fang, Yuanjian; Gao, Shiqi; Wang, Xiaoyu; Cao, Yang; Lu, Jianan; Chen, Sheng; Lenahan, Cameron; Zhang, John H.; Shao, Anwen; Zhang, Jianmin (Frontiers in Cellular Neuroscience, 2020)
Hemorrhagic stroke is a life-threatening neurological disease characterized by high mortality and morbidity. Various pathophysiological responses are initiated after blood enters the interstitial space of the brain, compressing the brain tissue, and thus causing cell death. Recently, three new programmed cell deaths (PCDs), necroptosis, pyroptosis, and ferroptosis, were also found to be important contributors in the pathophysiology of hemorrhagic stroke. Additionally, blood-brain barrier (BBB) dysfunction plays a crucial role in the pathophysiology of hemorrhagic stroke. The primary insult following BBB dysfunction may disrupt the tight junctions (TJs), transporters, transcytosis, and leukocyte adhesion molecule expression, which may lead to brain edema, ionic homeostasis disruption, altered signaling, and immune infiltration, consequently causing neuronal cell death. This review summarizes recent advances in our knowledge of the mechanisms regarding these new PCDs, and reviews their contributions in hemorrhagic stroke and potential crosstalk between BBB dysfunction. Numerous studies revealed that necroptosis, pyroptosis, and ferroptosis participate in cell death after subarachnoid hemorrhage (SAH) and intracerebral hemorrhage (ICH). Endothelial dysfunction caused by these three PCDs may be the critical factor during BBB damage. Also, several signaling pathways were involved in PCDs and BBB dysfunction. These new PCDs (necroptosis, pyroptosis, ferroptosis), as well as BBB dysfunction, each play a critical role after hemorrhagic stroke. A better understanding of the interrelationship among them might provide us with better therapeutic targets for the treatment of hemorrhagic stroke.